Air Pollution Removal and Temperature Reduction by Gainesville's Urban Forest - Francisco Escobedo; Jennifer A. Seitz; Wayne Zipperer (EDIS)
FOR-216, a 3-page illustrated fact sheet by Francisco Escobedo, Jennifer A. Seitz, and Wayne Zipperer, discusses how Gainesville's urban forest helps remove air pollutants and estimates the value, in reduced health care costs of that reduction, and provides information on the reduction in temperature the trees provide. Includes management recommendations and references. Published by the UF School of Forest Resources and Conservation, May 2009.